Wages, government payments and other income of Indigenous and non-Indigenous Australians - Howlett, Monica; Gray, Matthew; Hunter, Boyd (My University, 2016)
This paper compares the level and source of income for Indigenous and non-Indigenous Australians using data from the 2011 wave of the Household Income and Labour Dynamics in Australia (HILDA). Three sources of income are considered: wages and salaries; government benefits; and income from businesses, investments and other private transfers. Consistent with many previous studies, Indigenous Australians have, on average, lower total income than non-Indigenous Australians, with this difference being largest for those who are full-time employed. The difference is also larger for males compared to females. In terms of non-wage income, Indigenous men and women receive a much smaller proportion of income from other sources than their non-Indigenous counterparts (primarily business and investment income). This is particularly the case for those who are not in the labour force (NILF). Correspondingly, government benefits constitute a higher proportion of income for the Indigenous population than for the non-Indigenous. This is true for both males and females, and for all labour force states, although the difference is largest for part-time employed and those who are NILF. Given Indigenous persons are also more likely to be unemployed than non-Indigenous persons, they are more likely to be dependent solely on government payments as a source of income at any one time. The implications of these findings are discussed, as well as directions for future research.
Australian Journal of Labour Economics
Keywords: Finance -- Income (Salary and Wages); Benefits and Payments; Culture -- Indigenous; Income, wealth and finances; Finance; Benefits and Payments; Culture; Income (Salary and Wages); Indigenous; Income, wealth and finances